ChemInform Abstract: Catalytic Organic Reactions on the Surface of Silver(I) Oxide in Water. Issue 25 (5th June 2015) - Ueno, Masaharu; Tanoue, Arata; Kobayashi, Shu
Abstract: A method for the Ag2 O‐catalyzed allylation of aldehydes in water is presented.